«Unclear Enemy»: Why the Guerrilla War in France in 1814 Failed - N. A. Mogilevskiy (Vestnik MGIMO-Universiteta)
Abstract: Author of the article analyzes the reasons of the fail of Napoleon’s attempts to set the guerrilla war in France during the campaign of 1814. While the forces of anti-Napoleonic coalition were standing near the border of France, Napoleon did his best to recruit his new army. But the human resources of France were exhausted, and that’s why Napoleon decided to set the guerrillia. But all his proclamations and even his orders were disobeyed - French people were too tired of incessant war, and Napoleon again decided to gain his goals on the battlefield. Besides author shows great efforts of Russian headquarters to avoid the guerrilla war. Alexander I and his allies in theirs proclamations declared that they were fighting only with Napoleon, but not with the French nation. That tactic gave a brilliant result and helped to avoid the patriotic uplift in France in 1814. In this propagandistic war Napoleon was defeated and that cost him his throne. The reasons of Napoleon’s fail, firstly, was the unclear image of the enemy. French emperor didn’t manage to unite French nation against the rival. On the contrary the French Emperor, his enemies managed (in their proclamations and personal conversations) to persuade the French people, that the allies had one enemy - the Emperor Napoleon, not the French nation, and the ultimate goal of war - to set peace on the European continent. That was exactly how the allies did set the disunity between Napoleon and his people. Ultimately, the combination of these factors was the reason that a guerrilla war never broke out in France.